NPR2 Variants Are Frequent among Children with Familiar Short Stature and Respond Well to Growth Hormone Therapy - Plachy, Lukas; Dusatkova, Petra; Maratova, Klara; Petruzelkova, Lenka; Zemkova, Dana; Elblova, Lenka; Kucerova, Petra; Toni, Ledjona; Kolouskova, Stanislava; Snajderova, Marta; Sumnik, Zdenek; Lebl, Jan; et al. (The Journal of clinical endocrinology and metabolism, 2020)
CONTEXT: The C-type natriuretic peptide receptor encoded by the NPR2 gene is a paracrine regulator of the growth plate; heterozygous NPR2 variants cause short stature with possible presence of different signs of bone dysplasia. To date, the effect of growth hormone (GH) treatment has been described in a few individuals with NPR2 gene variants with inconsistent results. OBJECTIVES: To identify NPR2 gene variants among children with familial short stature (FSS) and to describe their phenotype, including GH treatment response. DESIGN, SETTINGS AND PATIENTS: Out of 747 patients with short stature treated with GH in a single center, 87 with FSS met the inclusion criteria (pretreatment height ≤ -2 standard deviation in both the patient and the shorter parent, unknown genetic etiology). Next-generation sequencing methods were performed to search for NPR2 gene variants. The results were evaluated using the American College of Medical Genetics and Genomics guidelines. The GH treatment response (growth velocity improvement and height standard deviation score development over the first 5 years of treatment) was evaluated. RESULTS: In 5/87 children (5.7%), a (likely) pathogenic variant in the NPR2 gene was identified (p.Ile558Thr [in 2], p.Arg205*, p.Arg557His, p.Ser603Thr). Two children had disproportionate short-limbed short stature, 1 a dysplastic 5th finger phalanx. The growth velocity in the first year of GH treatment accelerated by 3.6 to 4.2 cm/year; the height improved by 1.2 to 1.8 SD over 5 years of treatment. CONCLUSIONS: NPR2 gene variants cause FSS in a significant proportion of children. Their GH treatment response is promising. Studies including final height data are necessary to assess the long-term efficacy of this therapy.
Keywords: Young Adult; receptory pro atriální natriuretický faktor; fenotyp; Male; kohortové studie; biologické markery; Child, Preschool; Dwarfism; Phenotype; growth hormone treatment; mladý dospělý; Biomarkers; Cohort Studies; následné studie; Adolescent; prognóza; Infant; Child; next-generation sequencing; dítě; Adult; Body Height; dospělí; mužské pohlaví; tělesná výška; jednonukleotidový polymorfismus; nanismus; familial short stature; mladiství; Follow-Up Studies; Receptors, Atrial Natriuretic Factor; předškolní dítě; NPR2; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; Humans; growth plate disorders; Human Growth Hormone; kojenec; Prognosis; lidský růstový hormon; Female